Congenital melanocytic kissing nevus on right eyelid - A rare phenomenon - Rita V Vora; Aishni J Shah; Trisha B Patel (Wolters Kluwer Medknow Publications, 2020)
Congenital divided melanocytic nevus is a rare form of melanocytic nevus, which presents in the upper and lower eyelids on one side. It comes to existence due to genetic alteration in cells, which arise from mosaicism and only 30 cases have been reported till now. We present a rare case of 66 years old female with kissing nevus on right eyelids with no ophthalmological or functional disturbances.